2018
DOI: 10.1111/gcb.14141
|View full text |Cite
|
Sign up to set email alerts
|

Coral bleaching is linked to the capacity of the animal host to supply essential metals to the symbionts

Abstract: Massive coral bleaching events result in extensive coral loss throughout the world. These events are mainly caused by seawater warming, but are exacerbated by the subsequent decrease in nutrient availability in surface waters. It has therefore been shown that nitrogen, phosphorus or iron limitation contribute to the underlying conditions by which thermal stress induces coral bleaching. Generally, information on the trophic ecology of trace elements (micronutrients) in corals, and on how they modulate the coral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(84 citation statements)
references
References 61 publications
4
79
1
Order By: Relevance
“…This indicates that corals under control conditions were able to regulate the loss in autotrophic capacities by maintaining or increasing heterotrophic activities. It is well known that plankton supplementation prevents damage to the photosynthetic apparatus (Borell & Bischof, ; Connolly, Lopez‐Yglesias, & Anthony, ; Ferrier‐Pagès, Sauzéat, & Balter, ; Tremblay, Gori, Maguer, Hoogenboom, & Ferrier‐Pagès, ), lowers coral bleaching susceptibility (Grottoli et al, ; Hughes & Grottoli, ) and can further enhance the re‐establishment of photosynthate transfer following heat stress (Tremblay et al, ). Hughes and Grottoli () showed that some coral species can increase rates of heterotrophic carbon acquisition in host tissues for almost a year following bleaching in order to either compensate for the autotrophic loss of energy or prevent the effect of subsequent elevated temperature.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that corals under control conditions were able to regulate the loss in autotrophic capacities by maintaining or increasing heterotrophic activities. It is well known that plankton supplementation prevents damage to the photosynthetic apparatus (Borell & Bischof, ; Connolly, Lopez‐Yglesias, & Anthony, ; Ferrier‐Pagès, Sauzéat, & Balter, ; Tremblay, Gori, Maguer, Hoogenboom, & Ferrier‐Pagès, ), lowers coral bleaching susceptibility (Grottoli et al, ; Hughes & Grottoli, ) and can further enhance the re‐establishment of photosynthate transfer following heat stress (Tremblay et al, ). Hughes and Grottoli () showed that some coral species can increase rates of heterotrophic carbon acquisition in host tissues for almost a year following bleaching in order to either compensate for the autotrophic loss of energy or prevent the effect of subsequent elevated temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Over three decades of experiments and observations have developed and refined the central bleaching paradigm (e.g., Cziesielski et al, ) whereby accumulation of reactive oxygen species (ROS), and/or reactive nitrogen species (RNS), leads to signaling cascades and in turn expulsion or xenophagy of the algal endosymbionts (Family: Symbiodiniaceae) from the coral host (Davy et al, ; Smith et al, ; Tchernov et al, ; Weis, ). An overwhelming body of evidence has repeatedly demonstrated that perturbations to environmental factors underpinning optimum metabolic functioning can all result in bleaching; notably, temperature (Levin et al, ; Tchernov et al, ; Tolleter et al, ), light (Downs et al, ; Lesser & Farrell, ), salinity (Aquilar et al, 2019; Gardner et al, ; Ochsenkühn, Röthig, D'Angelo, Wiedenmann, & Voolstra, ) as well as inorganic nutrients including CO 2 (Anthony, Kline, Diaz‐Pulido, Dove, & Hoegh‐Guldberg, ; Crawley et al, ), iron and other trace metals (Biscéré, Ferrier‐Pagès, Gilbert, Pichler, & Houlbrèque, ; Ferrier‐Pagès et al, ; Shick et al, ), and the nitrogen‐to‐phosphate ratio (Fabricius, Cséke, Humphrey, & De'ath, ; Pogoreutz et al, ; Wiedenmann et al, ). Stability of the symbiosis rests on fine‐tuned resource exchange of primary metabolic currencies—C, N, P, electron carriers, etc.—among the algal symbionts, host, and/or broader associated microbiome (Suggett, Warner, & Leggat, ).…”
Section: The Mechanistic Biological Network Underpinning Bleaching Sementioning
confidence: 99%
“…Over 2,600 papers ( ISI Web of Science search “coral” AND “bleaching,” August 15, 2019) have been published since 1998, whereby continually expanding knowledge gained has been periodically transformed by new tools and technologies that particularly advanced bleaching observations in nature or unlocked the biological mechanisms at play. Over the past 25 years, Global Change Biology has contributed as a major platform in disseminating many of the breakthroughs from the global scientific community, including the process of bleaching at fundamental biological levels (e.g., Chakravarti, Beltram, & van Oppen, ; Crawley, Kline, Dunn, Anthony, & Dove, ; Ferrier‐Pagès, Sauzéat, & Balter, ; Pogoreutz et al, ; Smith et al, ), bleaching susceptibility and tolerance patterns in nature (e.g., Grottoli et al, ; Osborne et al, ; Osman et al, ; Silverstein, Cunning, & Baker, ; Vega‐Thurber et al, ), and ensuing ecological cascades (e.g., Anthony et al, ; Bellwood et al, ; Benkwitt et al, ; Montefalcone et al, ; Osborne et al, ; Richardson et al, ; Wolff, Mumby, Devlin, & Anthony, ), and in turn how these processes and patterns inform management (e.g., Anthony et al, ; Logan, Dunne, Eakin, & Donner, ; Selig, Casey, & Bruno, ; van Hooidonk, Maynard, Liu, & Lee, ; Wolff et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Manuscript to be reviewed Guest et al, 2016;Morgan et al, 2017). It may also be due to lower UV light penetration that can exacerbate temperature stress (Courtial et al, 2017), or potentially from higher heterotrophy, which increases the supply of essential metals to the symbionts thus sustaining them through elevated temperatures (Ferrier-Pagès et al, 2018). This study further suggests that while turbid reefs are potentially more resilient to elevated SST, the mechanism/s responsible for this resilience remain unclear.…”
Section: Manuscript To Be Reviewedmentioning
confidence: 86%